Sarocladione, a unique 5, 10:8, 9-diseco-steroid from the deep-sea-derived fungus Sarocladium kiliense. Issue 24 (5th June 2019) - Fan, Shao-Qiang; Xie, Chun-Lan; Xia, Jin-Mei; Xing, Cui-Ping; Luo, Zhu-Hua; Shao, Zongze; Yan, Xiao-Jun; He, Shan; Yang, Xian-Wen
Abstract : Sarocladione was isolated from the deep-sea-derived fungus Sarocladium kiliense as the first example of a 5, 10:8, 9-diseco-steroid. Abstract : A novel ergostane, sarocladione (1 ), was isolated from the deep-sea-derived fungus Sarocladium kiliense, along with 20 known compounds. The structure of1 was determined mainly by a detailed analysis of its experimental and calculated NMR spectroscopic data. It is worth noting that1 was the first steroid bearing a 5, 10:8, 9-diseco moiety. All 21 compounds were tested for in vitro antitumor activities against five cancer cell lines. β-Sitostenone (7 ) and 4, 6-dihydroxyeudesmane (20 ) showed significant effects on HeLa-S3 cells with the IC50 values of 9.2 μM and 9.3 μM, respectively.